Creating comprehensive, youth centered, culturally appropriate sex education: What do young gay, bisexual, and questioning men want? - Pingel, Emily Sweetnam; Thomas, Laura; Harmell, Chelsea; Bauermeister, José A. (Sexuality Research and Social Policy, 2013)
We examined young gay, bisexual and questioning men's (YGBQM) experiences with school-based sex education as they sought to learn about sex and sexual health, and their suggestions for improving same-sex education resources. Thematic analysis of 30 in-depth interviews with YGBQM (ages 18-24) underscored the discrepancies between the existing school-based sex education curricula and YGBQM's perceived sex education needs. Our results show that many youths' sexuality and same-sex sexual behaviors are excluded in sex education lessons; however, YGBQM noted that they sought out other resources (e.g., websites) to answer their questions. We discuss YGBQM's ideas for the creation of a sex and sexual health website that would be tailored for youth like themselves, including topics and features that an ideal website would contain. In addition, we present recommended changes to existing school-based sexual education curricula.
Keywords: EDI; LGBTQIA2+; amériques; approches et analyses; hétérosexisme; identités LGBTQIA2+; jeunes adultes; ressource en ligne; régions géographiques; santé; santé sexuelle; sexualité; systèmes d'oppressions; thématiques; éducation sexuelle; états-unis; étude qualitative